Phylogenetic affiliation and antimicrobial effects of endophytic actinobacteria associated with medicinal plants: prevalence of polyketide synthase type II in antimicrobial strains - Gohain, Anwesha; Sarma, Rupak Kumar; Debnath, Rajal; Saikia, Juthika; Singh, Bhim Pratap; Sarmah, Rajeev; Saikia, Ratul (Folia microbiologica, 2019)
The most diverse and versatile endophytic actinobacteria are relatively unexplored potential sources of bioactive metabolites useful for different medical, agricultural, and other commercial applications. Their diversity in symbiotic association with traditionally utilized medicinal plants of northeast India is scantly available. The present investigation assessed the genetic diversity of endophytic actinobacteria (n = 120) distributed around the root, stem, and leaf tissues of six selected medicinal plants (Emblica officinalis, Terminalia chebula, T. arjuna, Murraya koenigii, Rauwolfia serpentina, and Azadirachta indica) from three different protected areas of evergreen forest-the Gibbon Wildlife Sanctuary (GWS), the Kaziranga National Park (KNP), and the North East Ecological Park (NEEP) of Assam, India. The samples were collected in two seasons (summer and winter). The overall phylogenetic analysis showed significant genetic diversity with 18 distinct genera belonging to 12 families. Overall, the occurrence of Streptomyces genus was predominant across all three sampling sites (76.66%), in both the sampling season (summer and winter). Shannon's and Simpson's diversity estimates showed their presence at A. indica (1.496, 0.778), R. serpentina (1.470, 0.858), and E. officinalis (0.975, 0.353). Among the site sampled, GWS had the most diverse community of actinobacteria (Shannon = 0.86 and Simpson = 0.557). The isolates were antagonistically more active against the investigated plant pathogenic bacteria than fungal pathogens. Further analysis revealed the prevalence of polyketide synthase genes (PKS) type II (84%) and PKS type I (16%) in the genome of the antimicrobial isolates. The overall findings confirmed the presence of biosynthetically active diverse actinobacterial members in the selected medicinal plants which offer potential opportunities towards the exploration of biologically active compounds.
Keywords: Endophytes; Seasons; houby; bakteriální proteiny; India; Bacterial Proteins; Polyketide Synthases; antibióza; Symbiosis; fyziologie bakterií; roční období; Phylogeny; léčivé rostliny; Fungi; endofyty; Bacteria; Bacterial Physiological Phenomena; Actinobacteria; symbióza; Plants, Medicinal; fylogeneze; Indie; Antibiosis; polyketidsynthasy